Avaliação da política pública de atendimento educacional especializado (AEE) da rede municipal de ensino de Maracanaú-CE - Freire, Julieta Telles Lopes (2024)
The public policy of special education emerges, in the Brazilian context, as an important instrument for implementing actions that aim to assist citizens in their constitutionally foreseen rights in order to promote equal opportunities for individuals who do not fit into the traditional model of education. The objective of this study is to evaluate the special education policy in the municipality of Maracanaú-CE, focusing on Specialized Educational Assistance (AEE), with a time frame from 2012 to 2023. The data collection techniques were interviews with school managers, AEE classroom teachers and regular classroom teachers from 6 school institutions that offer Specialized Educational Services in the municipality. It is noteworthy that the methodology used was qualitative in nature with analysis of the axis of the institutional trajectory, investigating the various political disputes between the actors participating in the public policy in question, from the perspective of In-Depth Assessment, (Rodrigues, 2008, 2011), thus bringing the proposed actions, in an attempt to explain the institutional trajectory of the aforementioned policy. Data analysis leads to the understanding that the Specialized Educational Assistance Program has been growing gradually, as well as the demand and supply of this type of teaching, and it was also possible to deeply understand the vision of school managers, teachers in AEE classrooms and teachers from regular classrooms in relation to inclusion and special education in the municipality of Maracanaú.